Auto industry strategy shaping of the Republic of Belarus with consideration of innovation process in the field of ADAS systems development - Generalov, Eduard V. (Journal of the Belarusian State University. Economics, 2018)
The Republic of Belarus nowadays invests significant funds in national auto industry development. Analysis of the output of light and heavy vehicles allows to conclude, that the volume of national demand will not overcome the 5 % of the total, accordingly 95 % of the volume should be successfully sold on a quite competitive markets of our closest neighbours. If all the car makers have roughly equal technical options for cars of the same category, the only way of increasing competitive ability for Republic of Belarus is to orient its highly developed information technology sphere (companies residents of High technology park) for implementation of advanced driver assistant systems. This will help to create a competitive product as well as decrease the economic and social impact from road traffic accidents, due to their signi ficant quantitative and severity reduction.